2019
DOI: 10.1177/0165551519827886
|View full text |Cite
|
Sign up to set email alerts
|

HOMPer: A new hybrid system for opinion mining in the Persian language

Abstract: Opinion mining is a subfield of data mining and natural language processing that concerns with extracting users’ opinion and attitude towards products or services from their comments on the Web. Persian opinion mining, in contrast to its counterpart in English, is a totally new field of study and hence, it has not received the attention it deserves. Existing methods for opinion mining in the Persian language may be classified into machine learning– and lexicon-based approaches. These methods have been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 41 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…To classify the textual viewers' comments using a supervised method, each comment should be first converted into a feature vector. It has been shown that n-gram features, TF-IDF, part of speech (POS), and lexical features are effective features for emotion recognition and sentiment analysis [22], [80]. The input textual comments are first preprocessed, then features are extracted from the preprocessed texts.…”
Section: Textual Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…To classify the textual viewers' comments using a supervised method, each comment should be first converted into a feature vector. It has been shown that n-gram features, TF-IDF, part of speech (POS), and lexical features are effective features for emotion recognition and sentiment analysis [22], [80]. The input textual comments are first preprocessed, then features are extracted from the preprocessed texts.…”
Section: Textual Feature Extractionmentioning
confidence: 99%
“…Low-order N-grams including unigram and bigram are used broadly in NLP tasks to capture textual context [80]- [82]. It has been shown that the combination of unigram and bigram features are effective for sentiment analysis [22]. TF-IDF is also a popular feature extraction scheme in NLP and text mining tasks.…”
Section: Textual Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basiri et al [23] exploited the DS theory for predicting the sentiment of users from their comments and Nemati and Naghsh-Nilchi [24,25] used DS theory in multimodal affective video retrieval. More recently, Basiri and Kabiri [26] used the DS theory for aggregating sentiment labels and combining supervised and unsupervised machine learning classifier results for sentiment analysis [27]. The remainder of the article is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al have used a heuristic approach for scheduling of virtual machine reservations in cloud data centres [10]. Basiri and Kabiri developed a machine learning-based approach for opinion mining, a subfield of data mining [11]. Sharma et al presented a genetic algorithm (GA) and ontology-based NLP frameworks for online opinion mining [12].…”
Section: Introductionmentioning
confidence: 99%